Xerostomia as a potential condition in patients Covid-19 with tetanus: A Case report: Serostomia sebagai kondisi potensial pada penderita Covid-19 disertai tetanus: Laporan kasus - Alamsyah Piliang; Dewi Zakiawati; Nanan Nur'aeny (Makassar Dental Journal PDGI Makassar, 2022)
Introduction: Xerostomia is a dry mouth condition caused by many factors, including the potential of neuroinvasiveness and neurotropism from severe acute respiratory syndrome-coronavirus-2 (SARS-Cov-2). Tetanus causes muscle spasm, rigidity, and also as a risk factor for xerostomia. Objective: To discuss the pathogenesis of xerostomia in patients with coronavirus di-sease-2019 (Covid-19) and tetanus. Case: A 66-year-old male was referred to Oral Medicine Department from Neurology De-partment. Extraoral showed dry and exfoliative lips. Intraoral showed one finger mouth opening, a brownish plaque in dorsum of tongue, no saliva pooling in floor of mouth. Polymerase chain reaction SARS-Cov-2 was positive. Patient was diagnosed with xerostomia. Management: Cleaning the oral cavity with gauze moistened of 0.9% NaCl and 0.12% chlorhexidine diglu-conate, and applying the vaseline album on lips. Conclusion: The pathogenesis of xerostomia is an important factor as po-tential consequence of patients with Covid-19 and tetanus due to damage the angiotensin converting enzyme-2. Keywords: xerostomia, Covid-19, tetanus, angiotensin converting enzyme-2